2022
DOI: 10.1002/pc.26825
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and self‐sensing properties of 3D printed continuous carbon fiber reinforced composites

Abstract: The additive manufacturing technology of continuous carbon fiber reinforced composites (CCFRCs) based on fused filament fabrication offers new opportunities for the preparation and application of composites. This study prepared CCFRCs with excellent mechanical properties based on 3D printing technology. At the same time, a stress–strain and damage sensing method for the CCFRCs is proposed. Research results show that the maximum tensile stress and tensile modulus of 3D printed CCFRCs are 3.36 times and 5.10 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…The resistance of the CF in the fingers varies with the load applied to the hand, and the minute variation in resistance can be used to assess the health of the fingers. Ye et al 37 demonstrated the potential of FDM‐printed CF/PLA composites for identifying finger motor joints.…”
Section: Carbon‐reinforced Pmcs and Their Applicationsmentioning
confidence: 99%
“…The resistance of the CF in the fingers varies with the load applied to the hand, and the minute variation in resistance can be used to assess the health of the fingers. Ye et al 37 demonstrated the potential of FDM‐printed CF/PLA composites for identifying finger motor joints.…”
Section: Carbon‐reinforced Pmcs and Their Applicationsmentioning
confidence: 99%
“…[ 4–8 ] Additive manufacturing technology has attracted abundant attention in a variety of manufacturing areas, including optical, automotive, aerospace, electronics, medical, and construction industries, as it can rapidly and efficiently produce 3D products with a wider variety of materials, complicated structures, and integrated functions. [ 9–15 ] Several 3D printing technologies utilized are thermoplastic extrusion (ME), electron beam melting (EBM), laminated object manufacturing (LOM), selective laser melting (SLM), direct ink writing (DIW), selective laser sintering (SLS), and stereolithography (SL). [ 16–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Tensile and bending experiments demonstrated that 3D printed composites exhibit significantly improved mechanical properties compared to pure resin matrix. 14 However, the inadequate impregnation of fiber tows presents high porosity and low-quality stability, and their mechanical properties are much lower than the theoretical value. 15,16 Feeding continuous fiber prepreg filaments is an alternate way to print CFRC to overcome the impregnating issue because the high-viscosity thermoplastic resin can impregnate the continuous fiber filaments before the 3D printing process and the porosity within the 3D printed composites is reduced.…”
Section: Introductionmentioning
confidence: 99%